Potency and use of chia mucilage coating containing propolis liquid extract for improves shelf-life of sea bass fillets - Coban, Mehmet Zülfü; Coban, Ozlem Emir (Wydawnictwo Uniwersytetu Przyrodniczego w Poznaniu, 2020)
Background. In this study the effects of the use of chia mucilage - CM coating in combination with propolis liquid extract - PLE on the physico-chemical (total volatile basic nitrogen - TVB-N, peroxide value - PV, thiobarbituric acid - TBA) and bacteriological (total viable count - TVC, psychrophilic bacteria count - PBC) quality properties of sea bass fillets during storage at 2°C, as well as its potency, were investigated. Materials and methods. The fillets were randomly separated into four lots and subjected to the following treatments by dipping: chia mucilage - CM, chia mucilage + 0.1% PLE, chia mucilage + 0.3% PLE and control (uncoated), then stored at 2°C. Results. The results showed that the chia musilage coating containing PLE was effective on TVC and PCA. While the shelf life of the control group was 8 days, the CM + 0.3% PLE group was 20 days. Conclusion. According to these results, it can be said that chia mucilage coating preserves the shelf life and quality of chilled seafood and can be used safely as a coating material. © by Wydawnictwo Uniwersytetu Przyrodniczego w Poznaniu.
Keywords: Chia mucilage; Edible coating; Propolis; Quality; Sea bass; Shelf-life